Task complexity and foreign language writing emotions as predictors of EFL writing performance - Wu, Libo; Halim, Hasliza Binti Abdul (Frontiers in Education, 2024)
Emotions and task complexity have gained scant attention in EFL writing. This study, based on control-value theory and positive psychology perspective, explores the relationship between task complexity, writing anxiety, writing boredom, writing enjoyment and the task complexity and writing emotions interaction on EFL writing performance among English major students in China educational context (N = 84). It has been found that difficult writing task can result in higher writing anxiety and lower writing boredom. By 6×2 between-subjects ANOVA, there is significant interaction of task complexity and different levels of writing anxiety, writing boredom and writing enjoyment for the dimensions of language fluency, complexity and accuracy among English major students in China educational context. This study is an initial step in extending the writing emotions and task complexity in the production of EFL writing, which promotes the mutual integration of emotion and cognition in EFL writing research and thus supplies the suggestions for task-based EFL writing instruction.